Hubungan Kejadian Bullying dengan Harga Diri pada Anak Usia Sekolah di SDN Wonorejo IV, Kabupaten Pasuruan - Marelita, Ayu Nisfani; Mashitah, Musthika Wida; Wahyusari, Shinta (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: This study aims to determine the relationship between bullying incidents and self-esteem in school-age children at SDN Wonorejo IV, Pasuruan District. Methods: This study used a quantitative research design with a cross sectional approach. The population of this study were all 5th and 6th grade students at SDN Wonorejo IV, Pasuruan Regency, totaling 76 students with a sample of 76 students. The technique used was total sampling. The research was conducted on November 21, 2024 to November 22, 2024. The research instrument used the Olweus Bully/Victim Questionnaire (OBVQ) and the Hare Self-Esteem Scale questionnaire. The results of bivariate analysis using rank spearman. Results: The p-value = 0.002 (P < 0.05) indicates a significant relationship between the incidence of bullying and self-esteem in school-age children at SDN Wonorejo IV, Pasuruan Regency. The results of the study have a correlation coefficient (rho) of (-0.345) which means that the strength of the correlation is sufficient and the direction of the correlation is negative, which means that the lower the incidence of bullying, the higher the self-esteem in school-age children. Conclusion: The results of this study indicate that there is a relationship between bullying events and self-esteem in school-age children. The results of this study are expected to increase knowledge about the negative impact of bullying on victims in school-age children and how to prevent school-age children from bullying.